(untitled) (Applied Biological Research, 2013)
The ethanolic and aqueous extracts of rhizomes of five medicinal plants (Agave sisaliana, Euphorbia royleana, Zantedeschia aetthiopica, Stephania glabra and Mirabilis jalapa), collected from Solan district of Himachal Pradesh (India), were assayed for antimicrobial activity against eight bacteria including some human pathogens. The ethanolic and aqueous extracts of these plants were less effective against Escherichia coli, Bacillus subtilis and Staphylococcus aureus whereas M. jalapa extract was ineffective against Shigella sp. The qualitative phytochemical analysis confirmed the presence of various phytochemicals like tannins, alkaloids, saponins, steroids, phenols and glycosides in the rhizome extracts of these plants. The plant extracts tested possessed antimicrobial potential. Further, the presence of phytochemicals such as tannins, alkaloids, saponins, etc. in the rhizome extracts of these plants suggest their anticancer potential.